Carbon criminals, climate crimes - Kramer, Ronald C. (Critical issues in crime and society., 2020)
"Carbon Criminals, Climate Crimes analyzes the looming threats posed by climate change from a criminological perspective. It advances the field of green criminology through a examination of the criminal nature of catastrophic environmental harms resulting from the release of greenhouse gases. The book describes and explains what corporations in the fossil fuel industry, the US government, and the international political community did, or failed to do, in relation to global warming. Carbon Criminals, Climate Crimes integrates research and theory from a wide variety of disciplines, to analyze four specific state-corporate climate crimes: continued extraction of fossil fuels and rising carbon emissions; political omission (failure) related to the mitigation of these emissions; socially organized climate change denial; and climate crimes of empire, which include militaristic forms of adaptation to climate disruption. The final chapter reviews policies that could mitigate greenhouse gas emissions, adapt to a warming world, and achieve climate justice"--